2020
DOI: 10.1371/journal.pone.0242510
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary validation of the use of IgG antibody response to Anopheles gSG6-p1 salivary peptide to assess human exposure to malaria vector bites in two endemic areas of Cameroon in Central Africa

Abstract: The specific immune response to the Anopheles salivary peptide could be a pertinent and complementary tool to assess the risk of malaria transmission and the effectiveness of vector control strategies. This study aimed to obtain first reliable data on the current state of the Anopheles gSG6-P1 biomarker for assess the level of exposure to Anopheles bites in high malaria endemic areas in Cameroon. Blood smears were collected from people living in the neighborhoods of Youpwe (suburban area, continental) and Mano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Despite the observed seasonal variation, the sero-prevalence was unexpectedly lower during the second dry season when more Anopheles mosquitoes were collected when compared to the first dry season. This suggests that gSG6-P1 seroprevalence is not reflected by mosquito density as supported by several other studies [ 17 , 22 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Despite the observed seasonal variation, the sero-prevalence was unexpectedly lower during the second dry season when more Anopheles mosquitoes were collected when compared to the first dry season. This suggests that gSG6-P1 seroprevalence is not reflected by mosquito density as supported by several other studies [ 17 , 22 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 83%
“…This is probably due to behaviour as younger children are expected to sleep early and more hours and here the effect of bed net use is more apparent compared to the other age groups who probably get exposed before sleeping hours. A few studies conducted in different settings including Senegal, Cameroon and in the Solomon Islands reported findings similar to this study, where they have documented no statistical significant association between exposure to Anopheles mosquitoes and age [ 22 , 38 , 39 ], gender or use of anti-mosquito strategies such as LLINs [ 22 ]. Contrary to these studies, other studies have reported that levels of anti-gSG6-P1 IgG responses varied significantly by village and age; e.g.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…After continuous exposure to mosquito bites, humans develop a humoral response against mosquito salivary proteins, and this can be useful for surveillance and as a biomarker for exposure to bites and malaria disease risk ( 42 ). Individuals living in an area where malaria is endemic develop a humoral immune response to some salivary antigens such as AgSAP, SAMSP1, SG6, and 5-nucleotidase but not to other proteins like AgTRIO ( 12 , 38 , 43 ). Future studies are needed to understand if combining several salivary proteins will be a better approach than using individual proteins for identifying exposure to mosquitoes and malaria disease risk in areas of endemicity.…”
Section: Discussionmentioning
confidence: 99%